Structural Behaviour of Precast Segmental Concrete Beams Under Static and Impulsive Loads - Tran, Thanh Duong (Curtin University, 2023)
This study investigated the behaviours of precast segmental concrete beams (PSCBs) under static, blast and impact loads, using numerical, experimental and analytical approaches. The objectives are to (i) unveil the static and dynamic working mechanisms of PSCBs; (ii) investigate the influences of various parameters on PSCB performances; (iii) evaluate the viability of using sustainable and durable materials for the construction of PSCBs; (iv) develop analytical models for design analysis of PSCBs.